PENGARUH LITERASI KEUANGAN PADA PENGGUNAAN E-WALLET TERHADAP PERILAKU PENGELOLAAN KEUANGAN GENERASI Z DI KOTA MAKASSAR - Trihandayani, Arini; Mira, Mira; Basir, Basri (LPPM - STIE SAKTI ALAM KERINCI, 2026)
The development of digital technology has driven increased e-wallet use among Generation Z, which can influence financial management behavior. This study aims to analyze the influence of financial literacy and e-wallet use on the financial management behavior of Generation Z in Makassar City. Using a quantitative approach with an explanatory research method, data were collected through a Likert-scale questionnaire from 111 respondents. Data were analyzed using Partial Least Squares (PLS) to examine the influence of financial literacy and e-wallet use on financial management behavior. The results show that financial literacy has a positive and significant effect on the financial management behavior of Generation Z in Makassar City. Furthermore, e-wallet use also has a positive and significant effect. This suggests that increased financial literacy and the use of digital payment technology can encourage better financial management behavior. The better a person's financial understanding and wise use of digital payment technology, the better their ability to manage their finances. Therefore, improving financial literacy education is crucial for the younger generation. Keywords: Financial Literacy, E-Wallet, Financial Management Behavior, Generation Z, Makassar City.